Aliphatic polyketones as classic yet new molecular ropes for structural diversity in organic synthesis. Issue 64 (30th June 2020) - Inokuma, Yasuhide; Yoneda, Tomoki; Ide, Yuki; Yoshioka, Shota
Abstract : Synthesis, reactivity, and recent chemistry developments regarding aliphatic polyketones are highlighted with respect to chain sequences. These classic compounds are still showing new research potentials. Abstract : Polyketone compounds play an important role in organic chemistry as a prominent source of reactivity and functionality. Their chemical properties vary widely depending on the ketone sequence in carbon chains. Although vicinal and β-polyketones have been used for more than 150 years, the recent development of new ketone sequences composed of alternating 1, 3- and 1, 4-diketones has demonstrated the further potential of polyketones as structurally flexible molecular ropes capable of derivatization to π-conjugated chromophores and molecular assemblies. In this Feature Article, we review the synthetic strategies and reactivities of polyketones with respect to their ketone sequence. Furthermore, recent research on polyketones with hybrid ketone sequences is also discussed, focussing on their structural diversity in chemical transformations including intramolecular cyclization and stereoselective oxidation.